(untitled) (MORPHEÚS: Digital Journal of Pfychology of the Marista University of Queretaro, 2024)
The study of suicidal behavior has been a topic that has gradually become more relevant, due to the increase in cases world-wide. However, although suicide is an extremely present issue in contemporary society, there have also been models of suicide since the beginning of human history, which due to different cultural and time contexts have been modified. Therefore, within this research is presented a systematic analysis of a suicide model that represented a great influence on the thinking of the so-called “Age of Enlightenment”, that is, the 18th century. This model is found in the book “The Sorrows of Young Werther”, by the author Johann Wolfgang Von Goethe; book that has played a great role in the study of suicidal behavior over time. In this regard, a clear analysis is established based on various theoretical contributions of suicidology in the psychological field.